2016
DOI: 10.1111/ejh.12791
|View full text |Cite
|
Sign up to set email alerts
|

Controversies on the prognostic value of interim FDGPET in advanced‐stage Hodgkin lymphoma

Abstract: Hodgkin lymphoma, even in advanced-stage, is a highly curable malignancy, but treatment is associated with short-term toxicity and long-term side effects. Early predictive markers are required to identify those patients who do not require the full-length standard therapy (and thus qualify for therapy de-escalation) and those patients who will not be cured by standard therapy (and thus qualify for therapy escalation). Multiple trials have assessed the value of 18 F-fluoro-2-deoxy-D-glucose positron emission tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Previous systematic reviews regarding PET adapted therapy in HL have been published [32][33][34]. The strength of our systematic review, lies within the fact that it was based on a comprehensive search, according to a defined protocol and search terms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews regarding PET adapted therapy in HL have been published [32][33][34]. The strength of our systematic review, lies within the fact that it was based on a comprehensive search, according to a defined protocol and search terms.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the studies by Gallamini et al (12,13) are methodologically seriously biased. The predictive value of interim 18 F-FDG PET/CT was generally lower in other comparable studies (21), and 2 recent studies (22,23) including advanced-stage lymphoma as part of their patient population showed interim 18 F-FDG PET/CT to have minor or no value in predicting prognosis. Three recent studies (24-26) on treatment intensification in interim 18 F-FDG PET/CT-positive patients were published, all lacking a randomized control arm with nonintensified treatments.…”
Section: Replymentioning
confidence: 71%
“…Consequently, the true benefit of treatment intensification in these patients could not be assessed. In addition, comparisons with historical studies that suffered from inadequate methodology and heterogeneous results are futile (21). We individually criticized all 3 of these studies for these issues (27)(28)(29).…”
Section: Replymentioning
confidence: 99%
“…17 Early interim PET-CT response assessment performed after two cycles of ABVD (PET-2), has been demonstrated to be a powerful predictor of outcome, although both negative and positive predictive value have varied in cohort studies and retrospective analyses. 1825 Standardization of response assessment with FDG PET has been important to prospective study design, and our subsequent understanding of results from PET-guided treatment strategies. While the cut-off levels of uptake defining a negative or positive interim scan have varied between trials, these criteria have allowed identification of patients who could be considered for studies aiming to improve outcome of high-risk patients by intensification of their treatment (escalation) and to minimize exposure to toxic drugs without compromising the efficacy of therapy for low-risk patients (de-escalation).…”
Section: Introductionmentioning
confidence: 99%